A simulation model for evaluating the cargo transfer alternatives in liquid cargo terminals. (January 2023) - Deniz Özkan, Emin; Koçer, Umay Uzunoğlu; Nas, Selçuk; İşlek, Özgür; Tüzgen, Emel; Doğan, Anıl
Tanker ships arriving at liquid cargo terminals have to wait for getting service due to various operational restrictions in the terminal. Waiting time is the time passed until the tankers get service after the notice of readiness. The increase in the waiting times of tanker ships causes high demurrage costs. Reducing the waiting times of ships is of vital importance for the operational efficiency of the terminal. In this study, it is aimed to develop a simulation model in which alternative solutions in the cargo transfer operations can be tested to reduce the waiting times of tanker ships. The simulation model has several constraints that can be encountered in liquid cargo terminals, and it can be adapted to any liquid cargo terminal. The developed model was then applied to a liquid cargo terminal in Turkey.